The LetA/S two-component system regulates transcriptomic changes that are essential for the culturability of Legionella pneumophila in water - Nilmini Mendis; Peter McBride; Joseph Saoud; Thangadurai Mani; Sebastien P. Faucher (Scientific Reports, 2018)
Abstract Surviving the nutrient-poor aquatic environment for extended periods of time is important for the transmission of various water-borne pathogens, including Legionella pneumophila (Lp). Previous work concluded that the stringent response and the sigma factor RpoS are essential for the survival of Lp in water. In the present study, we investigated the role of the LetA/S two-component signal transduction system in the successful survival of Lp in water. In addition to cell size reduction in the post-exponential phase, LetS also contributes to cell size reduction when Lp is exposed to water. Importantly, absence of the sensor kinase results in a significantly lower survival as measured by CFUs in water at various temperatures and an increased sensitivity to heat shock. According to the transcriptomic analysis, LetA/S orchestrates a general transcriptomic downshift of major metabolic pathways upon exposure to water leading to better culturability, and likely survival, suggesting a potential link with the stringent response. However, the expression of the LetA/S regulated small regulatory RNAs, RsmY and RsmZ, is not changed in a relAspoT mutant, which indicates that the stringent response and the LetA/S response are two distinct regulatory systems contributing to the survival of Lp in water.